Ong Chyuan owning his dreams in the face of adversity, one step at a time - Prembaj, Divya (Property Insight, 2016)
Ong Chyuan sits effortlessly in his chair, hands clasped easily on the table in front of him. A glance at him, one would think that he would be your average young, mid-20's Malaysian youth, just starting out on his journey to seize his path in life. But standard and ordinary, he is not.